Погрешности определения высоты перехода к лёгким ионам при исследовании ионосферы методом некогерентного рассеяния - Котов, Дмитрий Владимирович; Богомаз, Александр Викторович (НТУ "ХПИ", 2015)
Исследованы погрешности высоты перехода к лёгким ионам, измеряемой с помощью метода некогерентного рассеяния. Проведено моделирование решений прямой и обратной радиофизических задач. Результаты моделирования свидетельствуют о том, что главный вклад в погрешность определения высоты перехода к лёгким ионам вносят статистические погрешности измерений относительных концентраций ионов водорода и гелия. Методические погрешности малы по сравнению со статистическими.

Errors in light ions transition height measured by incoherent scatter technique are studied. Simulation of direct and inverse radiophysical problems‘ solutions are made. The most correct model (radar ambiguity function that was calculated using actual pulse response of radar‘s receiver and pulse envelope) was used to simulate ACFs of IS signal and the results of inverse radiophysical problem solution. The results demonstrate that main contribution to the error in light ions transition height is the statistical errors in hydrogen and helium ions fractions. Methodical errors are small as compared with statistical ones. Standard deviation of the measured light ions transition height doesn‘t exceed 20 km when one use 15 ACFs of IS signal averaged over the interval of 15 min.
Errors in the light ions transition height estimation in the study of ionosphere by means of incoherent scattering technique
Keywords: радар; моделирование; импульс; сигнал; radar; simulation